Mapping agricultural performance and environmental parameters aimed at generic regional studies - Bakos, Károly Livius; Dobos, Attila; Nagy, János (Acta Agraria Debreceniensis, 2012)
In this paper we present the interim results and the methodology applied to create web GIS ready cartographic representations of agricultural performance related information and environmental parameters. The main aim of the research is to eventually create a web GIS based decision support system that can enable decsision makers and general users to create useful and representative map layouts of certain environment and agriculture related phenomena that can be easily analyzed and interpreted to make strategic decisions on environmental issues. In this aim the initial steps are to evaluate the available data for cartographic representation, analyze the possibilities of visualization, create a GIS ready data structure and implement the database and revise additional possibilities to incorporate further environment related datasets of auxiliary sources. The main results of the study are a comprehensive set of visual layouts that could serve as guideline for mapping statistical information of agriculture and some steps towards the incorporation of environmental parameters to the system.